2019
DOI: 10.1093/cid/ciz1140
|View full text |Cite
|
Sign up to set email alerts
|

Liver Stiffness at the Time of Sustained Virological Response Predicts the Clinical Outcome in People Living With Human Immunodeficiency Virus and Hepatitis C Virus With Advanced Fibrosis Treated With Direct-acting Antivirals

Abstract: Background Some people living with hepatitis C virus (HCV) with sustained virological response (SVR) develop hepatic complications. Liver stiffness (LS) predicts clinical outcome in people living with human immunodeficiency virus (HIV) with active HCV coinfection, but information after SVR is lacking. We aimed to analyze the predictive ability of LS at SVR for liver complications in people living with HIV/HCV with advanced fibrosis treated with direct-acting antivirals (DAA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…Degasperi et al [ 102 ] showed similar results in a retrospective study on 505 cirrhotic patients DAAs treated, demonstrating that a baseline LS > 30 kPa was an independent predictor of de novo HCC, being that the 3-year estimated incidence of de novo HCC was 20% in patients with LSM > 30 kPa versus 5% in patients with LSM ≤ 30 kPa ( p = 0.0003). Recently, in a population of 640 HIV/HCV co-infected patients followed for a median period of 31.6 months post-SVR by DAAs, with the aim of verifying the incidence of HCC, it was shown that none of the 374 patients with LS < 14 kPa at baseline developed HCC [ 103 ]. The authors suggest that the LS measurement may be helpful in selecting patients who may not be subjected to a tight surveillance program.…”
Section: Predictive Factors Of Hcc Appearance or Recurrencementioning
confidence: 99%
“…Degasperi et al [ 102 ] showed similar results in a retrospective study on 505 cirrhotic patients DAAs treated, demonstrating that a baseline LS > 30 kPa was an independent predictor of de novo HCC, being that the 3-year estimated incidence of de novo HCC was 20% in patients with LSM > 30 kPa versus 5% in patients with LSM ≤ 30 kPa ( p = 0.0003). Recently, in a population of 640 HIV/HCV co-infected patients followed for a median period of 31.6 months post-SVR by DAAs, with the aim of verifying the incidence of HCC, it was shown that none of the 374 patients with LS < 14 kPa at baseline developed HCC [ 103 ]. The authors suggest that the LS measurement may be helpful in selecting patients who may not be subjected to a tight surveillance program.…”
Section: Predictive Factors Of Hcc Appearance or Recurrencementioning
confidence: 99%
“…LSM, which has already found its way into the recommendations for the management of PH in 2015, ( 10 ) has been used to predict liver‐related events following SVR in two recent studies. Corma‐Gomez et al ( 30 ) reported an independent association of LSM with a composite endpoint of hepatic decompensation, HCC, OLT, and mortality in patients co‐infected with HIV/HCV who achieved HCV cure. However, although such a composite endpoint increases statistical power, it negatively affects the granularity of results, as the dynamics of PH do not necessarily relate to HCC risk after HCV cure.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, to mitigate the risk of type II error due to the limited number of patients undergoing paired invasive HVPG measurements, we evaluated the effect of the presumably most impactful variant (i.e., PNPLA3 ) on changes in well-validated surrogates of portal hypertension [ 13 ]. Importantly, these markers may confer prognostic information, even beyond their association with HVPG [ 33 , 34 ], and post-treatment LSM and VITRO have previously been shown to predict direct endpoints after SVR, such as the development of hepatic decompensation and HCC [ 14 , 35 , 36 ]. We observed a clear association between the PNPLA3 rs738409 G -allele carriage and pre-treatment severity of hepatic dysfunction and portal hypertension, which is in line with the previous literature [ 20 ].…”
Section: Discussionmentioning
confidence: 99%